Are sirtuins viable targets for improving healthspan and lifespan? - Baur, Joseph A.; Ungvari, Zoltan; Minor, Robin K.; Le Couteur, David G.; de Cabo, Rafael (Nature reviews. Drug discovery, 2012)
Key Points Caloric restriction is known to retard ageing and delay functional decline as well as the onset of disease in most organisms. Mammalian sirtuins (SIRT1–SIRT7) have roles in nutrient sensing, energy metabolism and genome stability, and may mediate some of the effects of caloric restriction. Sirtuin 1 (SIRT1), the most studied of the sirtuins, is an unusual target for drug development because it exerts many different effects that are relevant to health and could have a role in lifespan modulation via caloric restriction. Sirtuin-activating compounds are the subject of a growing field in medicinal chemistry, and several SIRT1 activators have been described, including resveratrol and SRT1720. Resveratrol and SRT1720 have been shown to increase healthspan, improve insulin sensitivity and alleviate other harmful effects of obesity in mice, but their mechanisms of action remain controversial. Many of resveratrol's effects on metabolism may be mediated by SIRT1-dependent deacetylation of PPARγ co-activator 1α (PGC1α), a key regulator of mitochondrial biogenesis, and involve AMP-activated protein kinase (AMPK), another key regulator of cellular energy homeostasis. Resveratrol promotes cardiovascular health, and evidence suggests that SIRT1 mediates the inhibitory effect of resveratrol on nuclear factor-κB (NF-κB) activity while also activating nuclear factor erythroid 2-related factor 2 (NRF2) and upregulating NRF2-driven antioxidant systems in endothelial cells. Resveratrol and sirtuins may have neuroprotective effects through several mechanisms, including reduction of inflammation, inhibition of plaque formation and activation of CREB-regulated transcription co-activator 1 (TORC1) signalling. Some recent studies suggest that the beneficial effects of resveratrol and the synthetic SIRT1 activators may also be realized in humans. This Review covers the current status and controversies surrounding the potential of sirtuins as novel pharmacological targets, with a focus on SIRT1. The sirtuin proteins have emerged as potential regulators of mammalian lifespan, and are believed to be responsible for the health and longevity-enhancing effects of caloric restriction. Here, Baur and colleagues provide an overview of the sirtuin family, focusing on sirtuin 1 (SIRT1) and its potential to be targeted in the treatment of age-related diseases. They address the controversy surrounding the mechanism of action of resveratrol and the development of more potent SIRT1 activators. Although the increased lifespan of our populations illustrates the success of modern medicine, the risk of developing many diseases increases exponentially with old age. Caloric restriction is known to retard ageing and delay functional decline as well as the onset of disease in most organisms. Studies have implicated the sirtuins (SIRT1–SIRT7) as mediators of key effects of caloric restriction during ageing. Two unrelated molecules that have been shown to increase SIRT1 activity in some settings, resveratrol and SRT1720, are excellent protectors against metabolic stress in mammals, making SIRT1 a potentially appealing target for therapeutic interventions. This Review covers the current status and controversies surrounding the potential of sirtuins as novel pharmacological targets, with a focus on SIRT1.